2021
DOI: 10.1109/access.2020.3041555
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Formation Mechanisms of Methanol During Cellulose Insulation Aging Based on Molecular Dynamics Simulation

Abstract: In recent years, methanol has been proposed as a chemical indicator to assess the aging condition of cellulose insulation in oil-immersed power transformers. However, the formation mechanisms of methanol during cellulose degradation are not clear enough. In this paper, such formation mechanisms were studied using molecular dynamics simulation. Three main formation pathways of methanol were found and discussed. Analysis of the Mayer bonds of cellulose revealed that each atom of cellulose contributes differently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…This is due to the mutual influence of degradation between oil and paper in practical scenarios. Scholars such as Zheng et al [26] and Liu et al [27] have separately investigated the mechanisms leading to the production of CO2 and methanol during cellulose degradation. Cong et al [13] explored the impact of vegetable oil and mineral oil on the degradation of insulating paper.…”
Section: Study On Aging Mechanisms Of Insulating Oilmentioning
confidence: 99%
“…This is due to the mutual influence of degradation between oil and paper in practical scenarios. Scholars such as Zheng et al [26] and Liu et al [27] have separately investigated the mechanisms leading to the production of CO2 and methanol during cellulose degradation. Cong et al [13] explored the impact of vegetable oil and mineral oil on the degradation of insulating paper.…”
Section: Study On Aging Mechanisms Of Insulating Oilmentioning
confidence: 99%
“…The results show that the ‐CH 2 ‐ group of C 5 group in cellobiose grabs the nearby H atom to form methanol. During the pyrolysis of cellobiose, methanol is stable in the early stage, but is unstable or even disappears in the later stage [47, 64].…”
Section: Formation Mechanism Of Methanolmentioning
confidence: 99%
“…The results showed that there are three main ways for the formation of methanol during the degradation of cellulose insulating materials. Liu et al [ 29 ] studied the generation path of ethanol at the atomic level through a series of ReaxFF-molecular dynamics (MD) simulations. The results show that (1) through molecular trajectory analysis, ethanol is mainly derived from vinyl alcohol, an intermediate product of pyrolysis of cellobiose.…”
Section: Alcohols Generation and Experimental Setupmentioning
confidence: 99%